SUPPLY CHAIN PERFORMANCE AND RISK ANALYSIS OF SIDIKALANG ARABICA COFFEE - Pusaka Sinulingga; Machfud Machfud; Depi Susilawati (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
Coffee is a commodity with significant business potential that has grown substantially in recent years. This research aims to identify the supply chain structure, analyze performance, and assess risks in the Sidikalang Arabica coffee supply chain, which is recognized for its geographical indication, to optimize its performance. The supply chain structure is analyzed using the Vorst method, while performance evaluation employs the Supply Chain Operations Reference (SCOR AHP) method, and risk assessment is carried out using the House of Risk (HOR) method. The study identifies six configurations in the Sidikalang Arabica coffee supply chain, primarily serving the hotel, restaurant, and café (HORECA) industry. Key supply chain members include farmers, micro, small, and medium enterprises (MSMEs), hotels, restaurants, and cafés. Performance analysis reveals that farmers, MSMEs, hotels, and restaurants fall into the medium category, scoring between 50%-70%, whereas cafés demonstrate strong performance with a 75% score. Risk analysis highlights that maintaining consistent quality standards significantly impacts consumer satisfaction and business sustainability. Optimization strategies include improving farmer cultivation, expanding MSME markets reach, diversifying products in the HORECA sector, and strengthening risk resilience. Meeting consumer demands with integrity reflects professionalism and enhances consumer satisfaction, ultimately supporting long-term business sustainability. Keywords: coffee, SCOR AHP, supply chain structure, supply chain performance, HOR